Boston Carpal Tunnel Questionnaire Scores Alone Do Not Predict Surgical Intervention for Patients With Carpal Tunnel Syndrome. (January 2023) - Chen, Frank R.; Kerluku, Jona; Manzi, Joseph E.; Chen, Aaron Z.; Nguyen, Joseph T.; Wessel, Lauren E.; Osei, Daniel A.; Fufa, Duretti T.
Background: With the expanded indications for telemedicine, there is increased utility for screening methods to determine which patients are likely to progress to surgical intervention, requiring in-person visits. Patient-rated tools such as the Boston Carpal Tunnel Questionnaire (BCTQ) may be one such tool for screening patients with carpal tunnel syndrome (CTS). The aim of the study was to evaluate whether BCTQ scores were predictive of offering conservative treatment or surgical intervention for CTS. Methods: Patients diagnosed with CTS from January 2017 to February 2020 completed BCTQ questionnaires prior to in-person office visits. Demographics, comorbidities, and highest level of intervention recommended were recorded for each patient as conservative, injection, or surgery. Pearson χ 2 and independent-samples t tests were conducted to determine whether BCTQ symptom severity and functional scores were associated with intervention type. Results: A total of 200 patients with CTS were included. Of these, 103 were recommended conservative or injection treatment and 97 were recommended surgery. There were no differences in comorbidities between groups, including other upper extremity pathology ( P = .57), previous upper extremity surgery ( P = .32), hypertension ( P = .17), hypothyroidism ( P = .15), rheumatoid arthritis ( P = .34), and diabetes ( P = .30). Between these groups, there were no differences in BCTQ symptom severity score (symptom severity scale [SSS]; P = .16) or BCTQ functional severity score (functional severity scale [FSS]; P = .96). Conclusions: There is no correlation between comorbidities and BCTQ SSS or FSS score, and offering surgery for CTS. In an era of minimizing non-essential health care visits, the BCTQ is insufficient in screening patients as potential surgical candidates.